Dephosphorylation of the HIV-1 restriction factor SAMHD1 is mediated by PP2A-B55α holoenzymes during mitotic exit - Kerstin Schott; Nina V. Fuchs; Rita Derua; Bijan Mahboubi; Esther Schnellbächer; Janna Seifried; Christiane Tondera; Heike Schmitz; Caitlin Shepard; Alberto Brandariz-Nuñez; Felipe Diaz-Griffero; Andreas Reuter; et al. (Nature Communications, 2018)
SAMHD1 is a critical restriction factor for HIV-1 and its antiviral activity is regulated by T592 phosphorylation. Here, Schott et al. show that the phosphatase PP2A-B55α dephosphorylates SAMHD1 during mitotic exit, rendering it antivirally active in G1 phase of primary CD4+ T cells.